Nurturing and Parenting: Dual Role of Parent on the Child Development and Socialization - Hidayati, Laily (ACIECE, 2016)
Many culture believe that parenting begins with birth, but the mother begins raising and nurturing a child well before birth. In the world of child development and socialization, there are two terms that have close meaning and interconnected. Two of the term is "nurturing" and "parenting". Nurturing refers to all the effort of environments in raising children. In practice includes the care of the food, drink, clothing, and shelter. It could be parent as nuclear family, grandparent, nonparental child care, or the significant others. This term nurturing, basically used to explain that there is other factor that build individual differences beside nature factor. This term want to make it clear that what make us different with others is how our environment treat us. Is where we live around. Usually, we got it from the first social group called â€œfamilyâ€. And family, consist of father and mother as parent, that in the end, we call it â€œparentingâ€. So the term "parenting" used to explain all the efforts of parents in raising children, by fulfilling the basic needs of children, covering the basic needs of growing up as a whole not only in terms of physical, biological, but also in terms of psychological and mental. That basic needs are need of stimulation, need of affection or compassion, and need of physical growth and development of biological care. Of course it includes education and cultivation of values, such as dicipline, respect, responsibility, etc. which is stained in the whole process of child development and socialization.